Violência e estado de exceção na Amazônia brasileira: um estudo sobre a implantação da hidrelétrica de Belo Monte no rio Xingu (PA) - NASCIMENTO, Sabrina Mesquita do (Universidade Federal do Pará, 2018)
The present thesis analyzes the violence of the implantation of the Belo Monte hydroelectric plant as the mechanism that produces the "fait accompli", constituting itself as a fact of the structure of the project. The State of Exception, according to the Italian philosopher Giorgio Agamben, is our interpretive key to understand the violence in Belo Monte, but our reflection also has the theoretical support of Pierre Bourdieu and his propositions about Symbolic Violence in the scope of state power . From this theoretical construction, it is defined that the thesis is directed to the understanding of the actions of government that made possible, especially the most recent ones. We operate such categories of analysis by observing how the production of consecutive illegalities exceeded the control system imposed on the licensing and implementation of the hydroelectric plant. Next, we focused on the suspension measures of the rules that ensured that irregular acts engendered during the environmental licensing and construction of the plant were disregarded. With this movement of analysis, we show how Belo Monte reveals the authority of political decision-making, which is present not only in the decision-making process itself, but also in legal rites, in the issuance of environmental licenses, and in judicial decisions that confirm the suspension of the norm as validity of that decision. The consequent production of an anomie zone in Belo Monte is what enables the continuous violation of rights practiced during the implementation of the project, which is projected in reality through various types of violence against the environment and the people of the Xingu.